SOCIAL DEMAND FOR A TEACHER-INNOVATOR - Ivan Syladiy ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
One of the necessary condition for the implementation of the concepts of democratization and humanization of education is the scientific and creative ability of teacher to self-development and selfimprovement. In this context, we note that according to experts, the following global phenomena significantly grow the need to increase the scientific capacity of the pedagogical process: informatization, digitalization, internationalization, virtualization of education, etc., where the teacher-innovator can introduce his own scientifically based opinion in the relevant scientific discourse, to develop and propose a new pedagogical technology or model of organization of managerial or educational work for implementation.